The forgotten threat of cholera in Syria. (22nd November 2022) - Al-Abdulla, Orwa; Alaref, Maher
Abstract: Cholera is an ancient disease that persists as an issue of public health in many conflict-affected countries worldwide. Cholera is a diarrheal infection caused by ingested water or food contaminated with the bacterium Vibrio cholerae. On 10 September 2022, the Ministry of Health in Syria declared a cholera outbreak. Poor water and sanitation systems, disease surveillance breakdown, the collapse of the health system, and deteriorated socioeconomic conditions are potential risk factors for the outbreak's spread. Identifying the context-related factors associated with the spread of disease is a core to developing practical response mechanisms. In this study, we suggested a multisectoral approach that addresses context-specific elements contributing to the cholera outbreak spread in Syria; public health determinants, geopolitics, risk factors, and pandemic fatigue. HIGHLIGHTS: A multisectoral approach that addresses context-specific elements contributing to outbreak spread. Indicates the potential for a practical and evidence-based household-centered community engagement approach. Presents the importance of covering the gaps in the cholera response due to the political and governmental instability by creating an inclusive field coordination mechanism. Graphical Abstract